Microwave-assisted synthesis, characterization and cytotoxic studies of novel estrogen receptor α ligands towards human breast cancer cells. Issue 8 (15th April 2015) - Bharathkumar, Hanumantharayappa; Mohan, Chakrabhavi Dhananjaya; Ananda, Hanumappa; Fuchs, Julian E.; Li, Feng; Rangappa, Shobith; Surender, Mohan; Bulusu, Krishna C.; Girish, Kesturu S.; Sethi, Gautam; Bender, Andreas; Basappa,; et al.
Graphical abstract: Abstract: A new, simple, and microwave-assisted, solution-phase T3P®-DMSO mediated method for the preparation of a novel class of estrogen receptor alpha (ERα) ligands based on the 2-phenylquinoline scaffold was developed. Furthermore, the novel ERα ligands were tested for their bioactivity against ERα-positive and ERα-negative cell lines. The ligand (entry 4), with amine and nitro group substitution at C4 position, displayed significant cytotoxicity against MCF-7 and HepG2 cells with an IC50 value of 6 and 11 μM, respectively. On the other hand, ERα-negative cells displayed resistance to quinolines induced cytotoxicity with an IC50 value >100 Mm and they does not induce cytotoxicity in normal breast epithelial cells. Molecular docking analyses suggest a consistent binding mode for these ERα ligands in the ligand binding domain of the human ERα and predict the ligands to occupy the hydrophobic cavity in a similar fashion as estradiol or GW2368.